1992
DOI: 10.1017/s0003356100037247
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary inclusion of yeast culture (Yea-Sacc) on patterns of rumen fermentation, food intake and growth of intensively fed bulls

Abstract: The effects of a barley beef diet without (control) and with a yeast culture (YC) on rumen fermentation, in vivo diet digestibility, nitrogen retention, live-weight gain and food intake were evaluated using 13 Limousin × British Friesian bulls per treatment. The YC was composed of the yeast species Saccharomyces cerevisiae and its growth medium dried in such a manner that it maintained its fermentative capacity. The addition of YC significantly increased the concentration of acetate (P < 0·05) while propion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
64
4
14

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 10 publications
17
64
4
14
Order By: Relevance
“…Our results are in accordance with those of other workers who found that supplementing yeast culture had no effect on the growth rate of intensively fed bulls (Mutsvangwa et al, 1992;El Hassan et al, 1996;Beauchemin et al, 2003), grazing steers (Cabrera et al, 2000) or lambs (Kawas et al, 2007). Others reported that yeast culture tended to reduce the average daily gain of steers (Mir & Mir, 1994) while Wehner et al (1998) found that yeast-fed calves tended to gain more than the control calves.…”
Section: Resultssupporting
confidence: 92%
“…Our results are in accordance with those of other workers who found that supplementing yeast culture had no effect on the growth rate of intensively fed bulls (Mutsvangwa et al, 1992;El Hassan et al, 1996;Beauchemin et al, 2003), grazing steers (Cabrera et al, 2000) or lambs (Kawas et al, 2007). Others reported that yeast culture tended to reduce the average daily gain of steers (Mir & Mir, 1994) while Wehner et al (1998) found that yeast-fed calves tended to gain more than the control calves.…”
Section: Resultssupporting
confidence: 92%
“…The results of other researchers are also inconsistent. Some investigators reported increased proportions of acetate (Mutsvangwa et al, 1992), while others found increased proportions of propionate (Plata et al, 1994). The hypothesis that considerable discrepancies are caused mainly by the ratio of structural to non-structural carbohydrates was not confirmed in our study using high-and low-fibre diets.…”
Section: Resultscontrasting
confidence: 90%
“…In the current study, no significant effects of LYC and YC were observed on effective degradation of NDF from maize grain and wheat straw, similarly as in other experiments (Mutsvangwa et al, 1992;Enjalbert et al, 1999). Live yeast culture in the low-NDF diet increased the degradation of NDF from wheat straw (P<0.05) after 6 h incubation (data not shown), but the rate of degradation and effective degradability were not modified.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…In contrast, Bach et al (2007) demonstrated that yeast supplementation (Saccharomyces cerevisiae Strain CNCM I-1077) to dairy cattle (5 g/day) contributes to the rumen environment by enhancing the ruminal pH. On the other hand, Mutsvangwa et al (1992) showed that ruminal pH was depressed by the addition of yeast culture (YeaSacc) in bulls (8 to 10 g/day). Nevertheless, one of the main effects of yeasts is to stabilise the rumen pH.…”
Section: Discussionmentioning
confidence: 99%